Localization and evolution of septins in algae. (7th March 2013) - Yamazaki, Tomokazu; Owari, Satomi; Ota, Shuhei; Sumiya, Nobuko; Yamamoto, Maki; Watanabe, Koichi; Nagumo, Tamotsu; Miyamura, Shinichi; Kawano, Shigeyuki
Summary Septins are a group of GTP‐binding proteins that are multi‐functional, with a well‐known role in cytokinesis in animals and fungi. Although the functions of septins have been thoroughly studied in opisthokonts (fungi and animals), the function and evolution of plant/algal septins are not as well characterized. Here we describe septin localization and expression in the green algae Nannochloris bacillaris and Marvania geminata. The present data suggest that septins localize at the division site when cytokinesis occurs. In addition, we show that septin homologs may be found only in green algae, but not in other major plant lineages, such as land plants, red algae and glaucophytes. We also found other septin homolog‐possessing organisms among the diatoms, Rhizaria and cryptomonad/haptophyte lineages. Our study reveals the potential role of algal septins in cytokinesis and/or cell elongation, and confirms that septin genes appear to have been lost in the Plantae lineage, except in some green algae.